2020
DOI: 10.1200/jco.19.01485
|View full text |Cite|
|
Sign up to set email alerts
|

Ten-Year Update of a Randomized, Prospective Trial of Conventional Fractionated Versus Moderate Hypofractionated Radiation Therapy for Localized Prostate Cancer

Abstract: PURPOSE The previously published single institution randomized prospective trial failed to show superiority in the 5-year biochemical and/or clinical disease failure (BCDF) rate with moderate hypofractionated intensity-modulated radiation therapy (H-IMRT) versus conventionally fractionated IMRT (C-IMRT). We now present 10-year disease outcomes using updated risk groups and definitions of biochemical failure. METHODS Men with protocol-defined intermediate- and high-risk prostate adenocarcinoma were randomly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…De Vries et al found significant improvement in local control in patients with a Gleason score = 8 treated with HFRT versus conventional schedule, but not in relapse-free survival [35]. Moreover, Avkshtol et al (Fox Chase) reported higher incidence of distant metastases at 10-year follow-up in patients in the HFRT arm (rate difference, 7.8%; 95% CI, 0.7% to 15.1%) and observed no between-group difference in overall survival [36]. Finally, the MD Anderson trial showed a 10.7% biochemical failure incidence in men treated with HFRT versus a 23.7% of incidence in patients treated with CFRT over a 10-year follow-up [25].…”
Section: Discussionmentioning
confidence: 98%
“…De Vries et al found significant improvement in local control in patients with a Gleason score = 8 treated with HFRT versus conventional schedule, but not in relapse-free survival [35]. Moreover, Avkshtol et al (Fox Chase) reported higher incidence of distant metastases at 10-year follow-up in patients in the HFRT arm (rate difference, 7.8%; 95% CI, 0.7% to 15.1%) and observed no between-group difference in overall survival [36]. Finally, the MD Anderson trial showed a 10.7% biochemical failure incidence in men treated with HFRT versus a 23.7% of incidence in patients treated with CFRT over a 10-year follow-up [25].…”
Section: Discussionmentioning
confidence: 98%
“…Multiple randomized trials and a meta-analysis evaluated the role of hypofractionated RT and concluded that its efficacy is equivalent to that of CF [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Data on whether HF increases overall treatment-related toxicity are inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…In designing the study, we did not seek to purposefully select participants based on gender since we felt attitudes towards IMRT and SBRT were unlikely to differ based on gender. Third, these interviews occurred in 2016 and more evidence has accumulated since then supporting hypofractionated radiation [33]. Nonetheless, SBRT is still sparingly used and, in the absence of randomized controlled data, these views are still very relevant today.…”
Section: Discussionmentioning
confidence: 99%